2021
DOI: 10.7150/thno.59196
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and genetic-based framework identifies drug targets in inflammatory bowel disease

Abstract: Rationale: With increasing incidence and prevalence of inflammatory bowel disease (IBD), it has become one of the major public health threats, and there is an urgent need to develop new therapeutic agents. Although the pathogenesis of IBD is still unclear, previous research has provided evidence for complex interplays between genetic, immune, microbial, and environmental factors. Here, we constructed a gene-microbiota interaction-based framework to discover IBD biomarkers and therapeutics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 75 publications
(98 reference statements)
0
11
0
Order By: Relevance
“…Currently, the pathogenesis of IBD remains incompletely understood. The use of IBD drugs is severely limited by low efficacy, side effects and intolerance (2). It was reported that probiotics could alleviate IBD by maintaining normal gut microbiota, enhancing mucosal barrier function, and inhibiting exposure to inflammatory signals, which are expected to be a new treatment for IBD (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the pathogenesis of IBD remains incompletely understood. The use of IBD drugs is severely limited by low efficacy, side effects and intolerance (2). It was reported that probiotics could alleviate IBD by maintaining normal gut microbiota, enhancing mucosal barrier function, and inhibiting exposure to inflammatory signals, which are expected to be a new treatment for IBD (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…One study reported data similar to ours, demonstrating that cGAS deficiency leads to increased intestinal inflammation and increased colitis‐associated tumorigenesis 22 . Another study that utilized a longer model of DSS colitis along with a higher percentage of DSS reported cGAS deficiency to be protective during the reparative phase of murine colitis 21 . The reasons for this discrepancy are unclear; however, differences in model design and/or facility microbiome profiles may play key roles 48 …”
Section: Discussionmentioning
confidence: 55%
“…22 Another study that utilized a longer model of DSS colitis along with a higher percentage of DSS reported cGAS deficiency to be protective during the reparative phase of murine colitis. 21 The reasons for this discrepancy are unclear; however, differences in model design and/or facility microbiome profiles may play key roles. 48 Understanding the effects of the host microbiome on IBD pathogenesis is crucial to gaining insight into the pathogenesis of disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations